Exploring overcrowding in social housing condominiums - Fuentes Maturana, Marco (Universidad de Chile. Facultad de Arquitectura y Urbanismo, 2012)
Through time, social housing condominiums, commonly known as “apartment blocks”, have evidenced a series of deficiencies that have become tangible through the construction of irregular renovations, the illegal appropriation of sites, the poor quality of the built form, etc. This article is part of a research project, done in 2011, that looked into the problems that the afore mentioned social housing typology presents, in order to propose solutions to them. This article is a synthesis of the fundamental observations retrieved in the research process, done through a series of semi-structured interviews to the inhabitants of two social housing complexes in the Metropolitan Region of Santiago, which concludes with a series of recommendations regarding the revision of the urban regulations that are currently in place.